Perbandingan Tingkat Kesehatan Masyarakat : Faktor Jaminan Kesehatan di Indonesia Dan Thailand - Meliani, Mila; Hafizh, Muhammad; Algifarry, Muhammad Hakim; Jeremia, Samuel Joseph; Setya, Saefa Faris; R, Rudiana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Health system is a term that includes individuals, institutions, financing, information, commodities and government governance strategies in providing prevention and treatment services to the community. This health system was created with the aim of responding to the needs and expectations of the community for health services in a fair and equitable manner. Then, good health services in countries really need reform, reorientation and revitalization. This research aims to determine the comparison of health systems in Indonesia and Thailand. The analytical study of the writing was carried out through a literature review. The country experiences many challenges in building strong and reliable healthcare. The health system in each country is very different, but one thing has the same goal, namely to improve the health status of the community at large. Each country has advantages and disadvantages to each health system implemented. The success of a country depends on enthusiasm, dedication, perseverance, hard work, good teamwork, ability (Human Resources, Facilities), sincerity of organizers, and community participation in achieving Universal Health Coverage in improving health status. better society.